Integrative GWAS reveals genetic determinants of salinity tolerance in barley under hydro and zinc oxide nano-priming - Yasser S. Moursi; Wesam W. Abozaid; Ahmed Shaaban; Mohamed A. Karam; Samar G. Thabet (Plant and Soil, 2026)
Background and aims Salinity stress severely reduces agricultural productivity worldwide, affecting crops at all growth stages. Enhancing yield under salinity requires understanding the genetic basis of morpho-agronomic traits. Barley ( Hordeum vulgare L. ), the fourth most produced cereal and relatively salt-tolerant, provides a useful model for such studies. Methods A panel of 150 spring barley genotypes was evaluated under field conditions, exposing plants to 200 mM NaCl from early reproductive stages until harvest. Treatments included hydro-priming and zinc oxide (ZnO) nanoparticle priming (100 ppm). Due to missing genotype data, one accession was excluded, and genome-wide association analysis (GWAS) was performed on 149 genotypes to identify loci associated with trait variation under salinity and priming. Results Significant genotypic variation was observed for all measured traits under salinity stress. Hydro-priming improved most traits overall, whereas nano-priming selectively enhanced heading date, thousand-kernel weight, number of spikelets per spike, and chlorophyll content, indicating treatment-specific physiological responses. GWAS identified 118 significant SNP-trait associations, including 16 multi-trait loci linked to salinity tolerance. On chromosome 3H, the sentinel marker SCRI_RS_204130 was associated with third-internode length under hydro-priming and with thousand-kernel weight under ZnO nano-priming, co-localized near a putative K⁺ transporter gene ( HORVU.MOREX.r3.3HG0297740 ). Two additional loci on 3H co-localized with zinc-finger genes ( HORVU.MOREX.r3.3HG0222050 and HORVU.MOREX.r3.3HG0286230 ) affecting spike length and thousand-kernel weight. Conclusion Collectively, these co-localized loci explain covariance among morpho-agronomic and yield-related traits under salinity stress. The results highlight hydro-priming as the more effective treatment and provide candidate markers for marker-assisted selection aimed at improving salinity tolerance in barley.